Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/srep00702
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall reductions over Southern Hemisphere semi-arid regions: the role of subtropical dry zone expansion

Abstract: Since the late 1970s, Southern Hemisphere semi-arid regions such as southern-coastal Chile, southern Africa, and southeastern Australia have experienced a drying trend in austral autumn, predominantly during April and May. The rainfall reduction coincides with a poleward expansion of the tropical belt and subtropical dry zone by around 2°–3° in the same season. This has raised questions as to whether the regional rainfall reductions are attributable to this poleward expansion. Here we show that the impact of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 28 publications
9
136
0
Order By: Relevance
“…2 (with a pattern correlation coefficient of 0.46, statistically significant at the 95% level): the rainfall increase over the high latitudes is still apparent, but there are larger zonal asymmetries compared with the warm season. Over the midlatitudes, the REwens depicts drying regions over the central Pacific and the Indian Oceans and over southern South America and southeastern Australia, in agreement with both GPCP data and with results from regional studies (for Australia, Delworth and Zeng 2014;Cai et al 2012). Note that there is a strong agreement between regions where rainfall increases (decreases) and the eddy activity and moisture availability increase (decrease).…”
Section: A the Climate Change Signal In The Sh As Depicted By The Resupporting
confidence: 72%
“…2 (with a pattern correlation coefficient of 0.46, statistically significant at the 95% level): the rainfall increase over the high latitudes is still apparent, but there are larger zonal asymmetries compared with the warm season. Over the midlatitudes, the REwens depicts drying regions over the central Pacific and the Indian Oceans and over southern South America and southeastern Australia, in agreement with both GPCP data and with results from regional studies (for Australia, Delworth and Zeng 2014;Cai et al 2012). Note that there is a strong agreement between regions where rainfall increases (decreases) and the eddy activity and moisture availability increase (decrease).…”
Section: A the Climate Change Signal In The Sh As Depicted By The Resupporting
confidence: 72%
“…This persistent rainfall deficit has been shown to be associated with changes in the global atmospheric circulation via the expansion of the Hadley circulation (estimated at 50 km per decade) and associated increase in pressure in the subtropical ridge, resulting in mid-latitude storm tracks being "pushed" further south (CSIRO, 2012;Whan et al, 2014). Cai et al (2012) also related the observed expansion of the Hadley Cell to a poleward progression of the tropical belt and subtropical dry zone, which they claim can explain most of the southeastern Australian rainfall decline. The expansion of the Hadley Cell can only be reproduced by global climate models when human influences (in the form of greenhouse gases, aerosols and stratospheric ozone) are included, leading to the assertion that the expansion is at least partially attributed to anthropogenic climate change (CSIRO, 2012;Lucas et al, 2012).…”
Section: The Big Dry In the Context Of Other Southern Hemisphere Droumentioning
confidence: 99%
“…Frequent drought events over the Southern Hemisphere subtropics have been mainly attributed to the recent poleward expansion and intensification of the descending branch of the Hadley Circulation [4]. Indeed, widespread droughts have affected recently several regions in the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%